2018
DOI: 10.1186/s12937-018-0417-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of dietary patterns, anthropometric measurements, and metabolic parameters with C-reactive protein and neutrophil-to-lymphocyte ratio in middle-aged and older adults with metabolic syndrome in Taiwan: a cross-sectional study

Abstract: BackgroundMetabolic syndrome is commonly associated with inflammation. The underlying factors of inflammation in metabolic syndrome are not fully understood. The objective of the study was to determine the association of dietary patterns, anthropometric measurements, and metabolic parameters with inflammatory markers in middle-aged and older adults with metabolic syndrome in Taiwan.MethodsA total of 26,016 subjects aged ≥35 y with metabolic syndrome were recruited from Mei Jau institution between 2004 and 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 55 publications
4
30
1
4
Order By: Relevance
“…Our results demonstrate that increased adipose tissue appeared to affect MRT and MRV and resulted in thinning of the macula. NLR, PLR and SIII, which can be simply and inexpensively calculated from complete blood count, have been shown to indicate subclinical inflammation in several previous studies (8,31,32,33). Furuncuoglu et al (33) showed that NLR, PLR, and SIII are positively correlated with BMI in adults.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our results demonstrate that increased adipose tissue appeared to affect MRT and MRV and resulted in thinning of the macula. NLR, PLR and SIII, which can be simply and inexpensively calculated from complete blood count, have been shown to indicate subclinical inflammation in several previous studies (8,31,32,33). Furuncuoglu et al (33) showed that NLR, PLR, and SIII are positively correlated with BMI in adults.…”
Section: Discussionmentioning
confidence: 95%
“…Furuncuoglu et al (33) showed that NLR, PLR, and SIII are positively correlated with BMI in adults. Another study of 26,016 adult patients determined positive correlation between NLR and MetS and obesity-related anthropometric data (32). One study of obese children with sleep apnea syndrome, a condition capable of leading to chronic hypoxia, showed that NLR and PLR increased with obesity (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 In addition, the western dietary pattern was revealed to be significantly associated with increased odds ratios of high CRP and NLR in both genders. 38 Monocytes play an important role in inflammation and atherosclerosis in MetS 39 and the production of inflammation cytokines. 40 The LMR has been recognized as a potentially predictive and prognostic maker for inflammation in distinct populations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, multiple studies have focused on assessing the role of NLR and PLR in patients with related-comorbidities; a study performed with 155 obese and non-obese patients with obstructive sleep apnea found significantly higher values in terms of NLR among obese individuals (46). Metabolic syndrome related obesity is another disorder commonly associated with chronic inflammation that was found to be related with NLR (48). Nevertheless, the findings remain contradictory because similar to our study, Bahadir et al also failed to prove an association between NLR and obesity or metabolic syndrome (49).…”
Section: Discussionmentioning
confidence: 99%